Altered disposition of drugs in acute renal failure rat models: drug development strategies and perspectives - Srinivas, Nuggehally R (Arzneimittelforschung, 2010)
In the evolving paradigm of drug development it is a reasonable strategy to avoid and/or anticipate potential risks in drug development for select drugs by performing in vitro and/or preclinical studies in appropriate animal models. The availability of acute renal failure (ARF) rat models provides an opportunity to explore the pharmacokinetic disposition of drugs and associated metabolites in conditions that mimic the pathophysiology of the disease in humans. Such studies may help in drug(s) selection for development, differentiating certain drug classes, and/or arriving at a dose strategy decision in the clinic.Scores of compounds, belonging to various therapeutic areas, have undergone pharmacokinetic investigations in ARF models induced by uranyl nitrate (CAS 10102-06-4), glycerol (CAS 56-81-5), cisplatin (CAS 15663-27-1) or gentamicin (CAS 1403-66-3) in rats. The published pharmacokinetic disposition data has unequivocally suggested that ARF conditions leads to decreased renal elimination of the drug and associated metabolites; however, the influence on the overall body clearance is dependent on the propensity of the contribution of renal versus non-renal mechanisms of elimination. In the case studies assembled for this review, 52.5% of the drugs showed an increased drug exposure, 35% of the drugs showed a decreased drug exposure and 12.5% of the drugs showed no altered exposure, in ARF rat models relative to control rats. Interestingly, ARF can have an overall impact on drug absorption, distribution, metabolism, local transport and biliary excretion. Hence, the overall pharmacokinetic disposition may have to be interpreted with caution during ARF since there is the potential for competiting pathways to co-exist. For instance, due to reduced renal elimination as a result of kidney insult caused by ARF, compensatory biliary excretion mechanism may occur. Alternatively, intestinal and/or hepatic enzymatic expression level may go up to facilitate enhanced metabolism. However, there may be instances where uraemic toxins floating in the circulation may block the metabolism and/or may also retard the absorption process.This review covers: 1) an illustration of a number of case studies providing tabulated information on the key altered pharmacokinetic parameters observed in ARF and the hypothesized mechanistic explanation; 2) a comprehensive description of altered absorption, distribution, metabolism, excretion and efflux transport related changes observed during ARF; 3) a general framework for drug development strategies and 4) a succinct discussion on the overall perspectives of the applicability of ARF rat models.
Keywords: Acute renal failure; Case studies; Pharmacokinetic parameters; Rat models